2006
DOI: 10.1136/emj.2005.028522
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of mortality among emergency medical admissions

Abstract: Background: The Rapid Acute Physiology Score (RAPS) and Rapid Emergency Medicine Score (REMS) are risk adjustment methods for emergency medical admissions developed for use in audit, research, and clinical practice. Each predicts in hospital mortality using four (RAPS) or six (REMS) variables that can be easily recorded at presentation. We aimed to evaluate the predictive value of REMS, RAPS, and their constituent variables. Methods: Age, heart rate, respiratory rate, blood pressure, Glasgow Coma Score (GCS) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
134
0
14

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(153 citation statements)
references
References 12 publications
5
134
0
14
Order By: Relevance
“…Several studies have shown that hospital mortality can be predicted on the basis of illness severity scores calculated at the time of admission, either in the emergency department, 18,19 an assessment unit 20,21 or a medical ward. 22 None of these studies looked at whether the average early warning scores varied according to time or day of admission; although such scores are somewhat blunt tools, this analysis may be a useful next step to help our understanding of the variation in mortality we have observed.…”
Section: Patient and Pre-hospital Factorsmentioning
confidence: 99%
“…Several studies have shown that hospital mortality can be predicted on the basis of illness severity scores calculated at the time of admission, either in the emergency department, 18,19 an assessment unit 20,21 or a medical ward. 22 None of these studies looked at whether the average early warning scores varied according to time or day of admission; although such scores are somewhat blunt tools, this analysis may be a useful next step to help our understanding of the variation in mortality we have observed.…”
Section: Patient and Pre-hospital Factorsmentioning
confidence: 99%
“…25,34 Little literature exists on risk assessment of undifferentiated emergency patients, and what there is concentrates on mortality risk. [35][36][37] It appears from the international experience that obesity, 17 pre-existing comorbidity 19 and pregnancy 17,38 convey a worse prognosis during pandemic influenza infection. A single study of bacterial pneumonic superinfection in influenza from Taiwan identified shock, respiratory rate of over 24 breaths/minute, acidosis, raised creatinine and a pneumonia severity index of class IV or V as indicators of poor prognosis.…”
Section: Chaptermentioning
confidence: 99%
“…However, heart rate and blood pressure as predictors are inconsistent in different studies. 4,13,19 One possible important explanation is that timing and quality of out-hospital resuscitation would influence these variables. Additionally, the finding that only GCS and HR predicted mortality may help understand why the scores have similar discriminatory power as both sub-components take part in each score.…”
Section: Resultsmentioning
confidence: 99%